PENERAPAN MEDIA E-BOOK BERBASIS APLIKASI GOOGLE PLAYBOOKS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA DALAM MATERI SISTEM IMUNITAS SMA NEGERI 4 KOTA PEMATANG SIANTAR TAHUN AJARAN 2021/2022 - NORAWIDYA F.M. SIALLAGAN; MASNI VERONIKA SITUMORANG; GUNARIA SIAGIAN (JURNAL ILMIAH KOHESI, 2022)
The purpose of this research is to improve student activities and learning outcomes in biology learning, specifically in the material of the human immune system, whose improvement efforts are carried out by applying e-book media based on the Google Playbooks application. The research used is a type of qualitative and quantitative research, because the problems brought are clearly related to research data in the form of facts proven through figures and facts that occur in the field through observation and analysis using statistics. The data collection method used is Quasy Experimental with a research design Pre test-Post test Control Group Design. The use of the Experimental Quasy method is based on considerations so that in the implementation students do not feel that they are being tested, so that all responses and actions that occur in research become more natural or natural. With such a situation it is expected to make a good contribution limited ...